(untitled) (Bangladesh Journal of Anatomy, 2011)
Body donation is the bequest of whole body after death for the purpose of medical research and education. Cadaver and donated bodies remains a principal teaching tool for the Anatomists teaching gross anatomy. Anatomy learning without hands on training of dissection on human bodies is never considered perfect. The Anatomy act provides for the supply of unclaimed bodies to the hospitals and teaching institutions for the purpose of anatomical examination and dissection and other similar processes. In this article, suitability of body donation, importance of body donation, various factors such as age, culture, personality characteristics, donor’s attitudes and role of mass media etc are discussed. Key words: Body donation; anatomy learning. DOI: 10.3329/bja.v8i2.7023 Bangladesh Journal of Anatomy July 2010, Vol. 8 No. 2 pp. 85-88